Diseño de un mariposario para la conservación de estas especies, que habitan en el área rural del cantón La Maná, provincia de Cotopaxi, 2015 - Figueroa Pincay, Verónica Maricela (2015)
Anthropogenic factors such as population growth, indiscriminate felling and agricultural green houses in which use fertilizers and pesticides, being the causes of many components for the destruction of the invertebrates habitat such as lepidoptera (butterflies), for this is necessary the construction of a bredding place of butterflies for the protection and conservation of the same is necessary, which is based on the research study field-descriptive by analytical, synthetic, inductive-deductive method, which was addressed to the population with a sample selected using investigation tools as the surveys, that it determined, that the development of the design of a breeding place of butterflies was benefiting directly to 30 familiar cores La Playita